2000
DOI: 10.1046/j.1365-2249.2000.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha (IFN-α) stimulates anti-melanoma cytotoxic T lymphocyte (CTL) generation in mixed lymphocyte tumour cultures (MLTC)

Abstract: SUMMARYIFN-a administration after primary tumour resection improves the survival of melanoma patients at high risk of relapse. To investigate whether this response might be due to stimulation of anti-tumour immunity, the effect of IFN-a on anti-melanoma CTL generation in MLTC was measured. IFN-a increased both allogeneic and autologous anti-melanoma CTL generation from peripheral blood lymphocytes stimulated with irradiated primary melanoma cultures. IFN-a up-regulated MHC class I expression on primary melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…For a long time, the importance of the effects of type I IFN on the immune system remained poorly considered (6). In recent years, however, some reports have shown that these cytokines affect the differentiation, survival, and function of immune cells, including T cells (7)(8)(9)(10)(11)(12)(13)(14)(15) and dendritic cells (DCs) 3 (16 -20) and efficiently enhance a primary Ab response (21). In a recent study it was shown that immunization of mice with chicken ␥-globulin in the presence of type I IFN results in the generation of a potent primary immune response, characterized by an isotype switching toward IgG2a Abs (21).…”
mentioning
confidence: 99%
“…For a long time, the importance of the effects of type I IFN on the immune system remained poorly considered (6). In recent years, however, some reports have shown that these cytokines affect the differentiation, survival, and function of immune cells, including T cells (7)(8)(9)(10)(11)(12)(13)(14)(15) and dendritic cells (DCs) 3 (16 -20) and efficiently enhance a primary Ab response (21). In a recent study it was shown that immunization of mice with chicken ␥-globulin in the presence of type I IFN results in the generation of a potent primary immune response, characterized by an isotype switching toward IgG2a Abs (21).…”
mentioning
confidence: 99%
“…41 It has been shown to stimulate anti-melanoma cytotoxic T lymphocytes in melanoma cell cultures. 42 Systemic IFN-␣ has been shown to improve disease-free and overall survival in advanced melanoma, 43 and intralesional IFN-␣ as therapy has been reported in melanoma 44 and in both LM and recurrent LM. 45 The successful use of topical imiquimod in the treatment of cutaneous neoplasia is presumably brought about by its ability to act as a potent apoptosis inducer and immune response-modifying agent through the induction of IFN-␣ and other cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…PBMC priming was associated with expansion of E75 ϩ TCR cells (more than 10-fold) and induction of E75 (21) due to a decrease in NS1 dimerization that partly impairs the ability of the NS1 to prevent IFN-␣/␤ synthesis in infected cells (49). Taking into consideration the recently reported effects of IFN-␣ on the induction of survival and maturation of CTLs (22,37), the use of vectors based on rIVs with truncated NS1 proteins may be a promising strategy for human cancer vaccination. CTLs induced by KIF-NS DCs specifically recognized the E75 peptide presented by HLA-A2 ϩ cells in cytokine assays.…”
Section: Discussionmentioning
confidence: 99%